Los múltiples rostros de la objetividad - Macarthur, David (Analysis. Journal of Philosophical Research, 2018)
In this paper I present a positive progressive picture of Putnam’s philosophy. According to this way of seeing things, Putnam is a normative cartographer of our linguistic practices who has over time refined his understanding of the concepts of truth and verification and their complex relationship from discourse to discourse. Looked at in this way Putnam is primarily a philosopher of objective normativity, who explores the various conceptions of objectivity with which we operate as well as resisting the excesses of both metaphysics and skepticism which do violence to our ordinary and scientific practices. However, Putnam sees himself as a philosopher of ‘reality’ focused on “the realism issue”, a metaphysically inflationary way of thinking that, I argue, stands in the way of his deepest insights